Turbulence in trying times "what are we to do" - Lin, See Yan (Pearson Malaysia Sdn Bhd, 2017)
"The book is essentially a follow-up on the first: The Global Economy in Turbulent Times, launched in June 2015. It picks up on developments covering the recent past two-and-a half years until June 2017. The book consists of essays which are rabid non-partisan, intended to always strike a balance with the idea that we often feel nothing really changes with the notion that yet, everything changes so fast, especially in the ever evolving internet of all things. Also, each essay hopes to initiate a conversation among readers and with leaders on serious global problems (especially in Asia), and how we should react and interact to make Malaysia a better place to work and live. The book gives an account of world affairs as they unfold since the beginning of 2015; faced then with a dismal global economic outlook where low oil prices and weakening currencies were causing havoc. It dissects why the world economy is broken and in urgent need of structural reforms, not just more stimuli or negative interest rates. It gives a run-down of why the United States continues to struggle with its jobless recovery; on why the eurozone economy is dead-on-its-tracks in constant fear of deflation, confronted with a recessive Greek tragedy; why Japan remains in deep hibernation; and why Brexit sets the United Kingdom adrift in, and Trump's election adds to new uncertainties to, an already turbulent world. The book also devotes much space to regional deveopments, giving an update on economic prospects in ASEAN, BRICS and MINT economies. It provides insights on happenings in and appraises the economic outlook for Asia, and China in particular. The final parts of the book deals with critical global issues of public concern - quality education, good leadership and dependable governance; innovation in search of higher productivity; demographic and climate change. The book offers a deep-dive into the range of problems raised and identifies solutions needed to get-out of the rut. The book ends on an optimistic note - on the dramatic turnaround in economic sentiment in early 2017 - pointing to a synchronised global upturn that appears to be already underway, which hopefully is broad-based and stable, no thanks to populism and nationalism"--Front flap